Urban-rural income disparity in the minority counties of Gansu, Western China - Feng, Jing (University of Ottawa (Canada), 2007)
China has been experiencing considerable growth following the economic reforms and open doors policy of 1978. The whole country has not benefited from these changes, however. A significant socioeconomic gap has been created between the developed Eastern coast and the poor hinterlands of the Western regions. Although the Chinese Government has made the development of the Western provinces' social and economic conditions a national priority (China's Western Development Priority), since the year 2000, progress has been hindered due to the lack of understanding of the many factors that have created the disparity of Western China. This thesis applies a statistical and geographical approach to understanding the evolution and spatial distribution of urban-rural income disparity in the minority counties of Gansu, Western China over the last 15 years. The quantitative analysis between this disparity and the socioeconomic variables reveal that minority counties are significantly affected by less favourable socio-economic environments. Moreover, urban-rural income disparity resuits in reduced access to basic education for school-aged children, particularly girls, in minority counties. This thesis adds a new perspective---statistical and geographical---to previous studies of urban-rural income disparity in Western China's minority regions.
Keywords: Geography.; Economics, General.